Association between TNF-a-308 G/A polymorphism and oral cancer risk among Malaysian Indian and indigenous / Mojtaba Golpich - Golpich, Mojtaba (2011)
The primary role of tumor necrosis factor alpha (TNF-α) gene is to regulate immune cells. Dysregulation and, in particular, overproduction of this gene has been found to increase susceptibility to a variety of human diseases such as cancer. The aim of this study is to investigate the association of single nucleotide polymorphism (SNP) in TNF-α −308 promoter and the risk of oral cancer among the Malaysian Indian and Indigenous population.The study included 143 confirmed oral squamous cell carcinoma (OSCC) (mean age = 63.69 ± 12.84) and 79 healthy controls (mean age = 50.43 ± 16.35). The polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) was employed to analyze TNF-α −308 promoter polymorphism, which were confirmed by direct sequencing. Chi-square, simple logistic regression and stratified analysis were performed using the SPSS (ver 15.0) to study the role of TNF-α polymorphism in modulating the risk of oral cancer. The wild-type genotype (GG) was seen in 88.8% (127) of OSCC patients in comparison to 87.3% (69) controls; while variant genotypes (GA & AA) were seen in 9.8% (14) and 1.4% (2) of cases and 11.4% (9) and 1.3% (1) of controls respectively. Also no significant association was observed between variant genotypes (GA & AA) and oral cancer risk. Polymorphism of TNF-α at position −308 G/A may not be a risk factor for oral cancer because we did not find a statistically significant association between the TNF-α −308 G/A polymorphism and oral cancer risk (p = .710 and p = .946 for GA and AA respectively). In conclusion, no association was seen between TNF-α −308 G/A polymorphism and oral cancer risk among the Malaysian Indian and Indigenous population.